Clinical significance of accessory foramina in adult human mandible - Goyal, Nisha; Sharma, Maneesha; Miglani, Rasalika; Garg, Anil; Gupta, P. K. (International Journal of Research in Medical Sciences, 2017)
Background: The mandible is the strongest and largest bone of facial skeleton. It consists of one horseshoe-shaped body and a pair of rami. On external surface of body in the midline there is a faint ridge i.e. symphysis menti indicating the line of fusion of two halves of mandible during development. The aim of this study is to describe the position and incidence of accessory foramina on the inner surface of the body and rami of both sides of mandible to provide simple important reliable surgical landmarks. Methods: The present study was conducted on 100 dried adult human mandibles. Bones which had deformities, asymmetries, external pathological changes and fractures were excluded from the present study. Results: In 97% cases at least one accessory foramen was observed on inner surface of mandible. The accessory lingual foramen was found to be constant finding with incidence of 81%. Frequency of infraspinous or sublingual foramen was 58%, of lateral foramen was 50% and that of accessory mandibular foramen was 39%. Conclusions: The anatomical knowledge about the common location and incidence of accessory foramina in mandible are important for surgeons and anaesthetists performing surgeries in the area around mandible. These accessory foramina transmit neurovascular bundles which provide accessory innervations to the roots of teeth. Thus proper knowledge of accessory foramina are important in relation to achieving complete inferior alveolar nerve block and for avoiding injury to neurovascular bundle passing through them.